A Study of Vipassana Practice in Padhaniyanga Sutta - Aphichai Tosang, Phrakruphunyapothikhat; Koomkrong, Viroj (Journal of Thammawat, 2023)
The purpose of this article is to study the principles or teachings contained in the Padhaniyanga Sutta and to study the practice of Vipassana. This research was conducted by qualitative analysis. Gather information from Theravada Buddhist scriptures and related documents. The results of the research showed that the principle in Padhaniyanga Sutta is the sutra that the Lord of the monks who persevere, meaning perseverance or the Lord of perseverance. Nirvana is a virtue that consists of faith, that is, having faith, faith firmly in the jewels as verse 1. When there is faith and relying only on faith, it is not possible to perform full virtues if the person has a disease or a serious disease, then there will be no obstacles that are not smooth, namely the absence of paths, there is a terrible disease, 2. The next is to be honest with oneself and to those around him, it will surely make it dear to the common people, there is no devil as an obstacle to the development of Dhamma, is verse 3. This is the Lord of Perseverance that the Buddha said in the said sutra